ETIKA SECARA ISLAM SEBAGAI BENCHMARK DALAM GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH - Nia Tresniati (LPPM POLITEKNIK LP3I BANDUNG, 2016)
Based on some researches, there’s still unfair business practice and ethical problem in our society. In financial and banking industry, shariah bank has infraction ethical related to the product of financing particularly on forbidden contractual. The methodology of study is literature study, Interpretation of Al-Qur’an verses, and analyzing the research. The study s focused to the islamic ethic as benchmarking for corporate governance in shariah bank. In islamic lesson, the individual has ethical beliefs as a moral compass (command and prohibition from God) that helps guide a person for hereafter. Allah SWT has determined the effectively supervision mechanism with reward and punishment. Islamic principles then acts as early warning that can control their behavior. Therefore, each person in one organization has good internal control for their own ethics that can build integrity. If all people in organization have placed the ethical forward for their activities as guidance, it creates corporate culture with high integrity and trusteeship. Good ethic drives the organization to good corporate governance in shariah bank with the high quality performance based on prudential principles, its purpose to Allah SWT and society. Value proportions from bank shariah supposed to create the economic justice for universal human trait.